2022
DOI: 10.3389/fcell.2022.884677
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Fresh Embryo Transfers and Frozen–Thawed Embryo Transfers Regarding Live Birth Rates Among Women Undergoing Long Gonadotropin-Releasing Hormone Antagonist Protocols

Abstract: Background: The availability and use of frozen–thawed embryos after controlled ovarian hyperstimulation for assisted reproduction have increased with improvements in vitrification techniques and the rise of gonadotropin-releasing hormone (GnRH) antagonist protocols. Although evidence has shown that frozen–thawed embryo transfers (FETs) result in higher live birth rates than fresh embryo transfers, it is uncertain whether this association exists in cycles employing the GnRH antagonist protocol.Objective: To tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Nowadays it is also common practice in ART clinics to transfer frozen-warmed blastocysts for different reasons: no pregnancy after fresh embryo transfer, ovarian hyperstimulation syndrome and in particular in endometriosis patients embryo transfer may be delayed due to planned endometriosis surgery before embryo transfer if persisting endometriosis symptoms are present and/or endometrioma surgery is inevitable and is potentially threatening the ovarian reserve. To our knowledge, there is a lack of reliable data on pregnancy rates after fresh vs. frozen thawed embryo transfer in endometriosis related infertility but in a retrospective study of women without endometriosis treated with an antagonist protocol live birth rates in frozen-warmed embryo transfers where shown to be higher compared with fresh embryo transfer (Fan et al, 2022), while others did not show a benefit of a freeze-all strategy in comparison with a fresh embryo transfer (Feichtinger et al, 2019;Wong et al, 2021). As frozen-thawed embryo transfer is common practice it was chosen as inclusion criteria in this study, even though further investigation on its benefit is required.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays it is also common practice in ART clinics to transfer frozen-warmed blastocysts for different reasons: no pregnancy after fresh embryo transfer, ovarian hyperstimulation syndrome and in particular in endometriosis patients embryo transfer may be delayed due to planned endometriosis surgery before embryo transfer if persisting endometriosis symptoms are present and/or endometrioma surgery is inevitable and is potentially threatening the ovarian reserve. To our knowledge, there is a lack of reliable data on pregnancy rates after fresh vs. frozen thawed embryo transfer in endometriosis related infertility but in a retrospective study of women without endometriosis treated with an antagonist protocol live birth rates in frozen-warmed embryo transfers where shown to be higher compared with fresh embryo transfer (Fan et al, 2022), while others did not show a benefit of a freeze-all strategy in comparison with a fresh embryo transfer (Feichtinger et al, 2019;Wong et al, 2021). As frozen-thawed embryo transfer is common practice it was chosen as inclusion criteria in this study, even though further investigation on its benefit is required.…”
Section: Discussionmentioning
confidence: 99%
“…Although, there are some studies suggest that the administration of a rescue double GnRH antagonist dose at 1 day before hCG trigger may represent a safe alternative preventive strategy for preventing early OHSS without affecting the reproductive outcomes ( 12 ). However, more studies are pointing to embryo transfer in resuscitation cycles to improve clinical pregnancy rates and live birth rates and to reduce the occurrence of OHSS ( 13 , 14 ). There are many randomized controlled trials comparing the advantages and disadvantages of conventional whole embryo freezing and fresh cycle transfer strategies ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with those of Ferraz et al [ 24 ] who demonstrated a higher pregnancy rate with fresh embryos than with frozen embryos. This suggests that freezing affects the pregnancy rate of IVD embryos [ 25 ]. However, the present study revealed that frozen embryos transferred using the current freezing protocol exhibited pregnancy rates similar to fresh embryos.…”
Section: Discussionmentioning
confidence: 99%